Aerial Mechatronic Systems for Collection of Atmospheric and Environmental Data - Pop, S.; Ceocea, C.; Cioacă, C.; Prisacariu, V.; Boșcoianu, M.; Vlădareanu, V.; Vladareanu, L. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Currently, atmospheric and environmental monitoring also requires approaches based on robotic aerial mechatronic systems that can offer the advantages of onboard intelligent sensors. The accelerated dynamics of climate change generate risks that can be prevented by the acquisition, storage, transmission and processing of data taken under static, quasi-statistical and kinetic conditions at lower costs compared to piloted aircraft. The article presents an approach on atmospheric and environmental monitoring using a robotic aerial mechatronic system based on an airship UAV and a classic airborne UAV, launched using a ground-based launch device.